Association between Paramedic Workforce and Survival Rate in Prehospital Advanced Life Support in Out-of-Hospital Cardiac Arrest Patients - Kichan Han; You Hwan Jo; Yu Jin Kim; Seung Min Park; Dong Keon Lee; Dong Won Kim; Kui Ja Lee; Hyo Ju Choi; Dong-Hyun Jang (Emergency Medicine International)
The low survival rate of out-of-hospital cardiac arrest (OHCA) patients is a global public health challenge. We analyzed the relationship between the number of prehospital EMS personnel and survival admission, survival discharge, and good neurologic outcomes in OHCA patients. This was a retrospective observational study. Adult nontraumatic OHCA patients from January 1, 2015, to December 31, 2018, were included from 12 cities in the Gyeonggi province, a metropolitan area located in the suburbs of the capital of the Republic of Korea. By comparing the insufficient EMS team (four or five EMS personnel) and the sufficient EMS team (six EMS personnel), we showed the survival rate of each group. Using propensity score matching, we reduced the bias of the confounding variables. A total of 3,632 OHCA patients were included. After propensity score matching, survival to admission was higher in the sufficient EMS team than in the insufficient EMS team (odds ratio (OR): 1.38, 95% confidence interval (CI): 1.04–1.84, P=0.03). Survival-to-discharge was similar (OR: 1.70, CI: 1.20–2.40, P=0.03), but there was no significant outcome in good neurologic outcomes (OR: 0.88, CI: 0.57–1.36, P=0.58). Our findings suggest that a sufficient EMS team (six EMS personnel) could improve the survival admission and discharge of OHCA patients compared to an insufficient EMS team (four or five EMS personnel). However, there was no significant difference in neurologic outcomes according to the number of EMS personnel.